Social discourse and moral judgment - Robinson, Daniel N., 1937- (Academic Press, 1992)
This edited work presents a unique and authoritative look at morality - its development within the individual, its evolution within society, and its place within the law. The contributors represent some of the foremost authorities in these fields, and the book represents a collection of essays presented at a symposium on social constructivism and morality.